Home Economics education and related subjects as catalysts in the prevention of HIV/AIDS Ethiopia - Daba, Eden Mengistu; Orlina, Elsa A. (2004)
This study aimed to determine what programs concepts/knowledge and values are taught in Home Economics and related subjects for the prevention of HIV/AIDS and to identify the predictors of the effective management of HIV/AIDS Prevention Program in the Educational System at all levels in Awassa City, Ethiopia. Respondents were 75 elementary, 75 high school, 62 college students and 75 teachers from six public and private schools who responded to a researcher-made questionnaire. A total of 30 participants divided into four groups participated actively in the Focus Group Discussions. Documentary Analyses were also used in analyzing the existing curricula and teaching guides in Home Economics and other related subjects. Mean, Regression and ANOVA were the statistical tools used. Significant level was set at 0.05. Majority of the respondents were single, 22 years old, Christians, males with only one HIV/AIDS-related training program attended. The teachers had 15 years of teaching experience. Collectively, the level of management effectiveness of HIV/AIDS prevention programs was perceived to be high (x 3.46). However, by category the process of undertaking the HIV/AIDS Prevention Program was relatively low (x 2.99). Data gathered show that the significant predictors of effective management were school/institution support, discussion on sex-related topics at home and age. The overall perception of respondents of the effective management of HIV/AIDS Prevention Program of student and teacher groups was significant. The stakeholders of the program and curriculum developers should give attention to the implementation (process) of the HIV/AIDS Prevention Program. Findings from documentary analyses, show that Home Economics and related subjects such as Biology and Science do not integrate HIV/AIDS prevention in their curricula. There is still a need to give more focus and attention in addressing the issue. As a humanizing discipline, Home Economics ultimate goal is to improve the quality of life of the individual and his family. Hence, the Home Economics professionals should refocus their curriculum and exert active participation in the implementation of programs for the prevention of HIV/AIDS Pandemic. All sectors, NGO's, government and particularly the church need to be tapped. Although there are annual activities or programs related to the prevention of HIV/AIDS Pandemic, these are seasonal, fragmented and making a shallow dent of awareness particularly among rural people. More effective and pragmatic collaboration will be made if one has to arrest a pandemic which is not only affecting a country and its people but a problem which indicate some global implications and perspective.
Keywords: Home economics -- Ethiopia; HIV prevention -- Study and teaching -- Ethiopia; Health education -- Ethiopia; AIDS prevention -- Study and teaching -- Ethiopia